Exergy and exergoeconomic evaluation of hydrogen and distilled water production via combination of PEM electrolyzer, RO desalination unit and geothermal driven dual fluid ORC. (1st December 2018) - Kianfard, Hossein; Khalilarya, Shahram; Jafarmadar, Samad
Highlights: A geothermal based system is presented in order to produce hydrogen and distilled water. A Dual fluid ORC is employed to harvest the thermal energy into power. A PEM electrolyzer and an RO desalination unit are employed to produce hydrogen and water, respectively. Exergy analysis is used to find the highest irreversibility source of the presented system. Exergy based economic analysis is adopted to estimate the cost of produced hydrogen and water. Abstract: Exergy and Exergoeconomic analysis are carried out for a new hydrogen and distilled water producing system. The presented cogeneration system is the combination of geothermal driven dual fluid organic Rankine cycle (ORC), proton exchange membrane (PEM) electrolyzer and reverse osmosis (RO) desalination unit. In fact, hot geothermal water is the system input energy, which turns into power and runs the PEM electrolyzer and RO unit. Exergy analysis revealed that the ORC has the highest exergy destruction among the all main units and causes 59% of the total exergy destruction. Also, within the ORC, low pressure evaporator has the highest exergy destruction compared with other components. An increase in the geothermal water temperature resulted in a reduction in system overall exergy efficiency. Furthermore, exergoeconomic analysis showed that 56% of the total investment cost refers to the ORC. Based on the exergoeconomic analysis and considering the unit exergy cost of 1.3 $/GJ for geothermal hot water, produced hydrogen and distilled water have costs of 4.257 $/kg and 32.73 cent/m 3, respectively. Moreover, the annual payback period of 5.6 years indicates that the presented system can be of interest from the viewpoint of initial investment.